New technologies and employment: the state of the art - Marco Vivarelli; Guillermo Arenas Díaz (Global Labor Organization (GLO), 2025)
The relationship between technology and employment has long been a topic of debate. This issue is even more pertinent today as the global economy undergoes a technological revolution driven by automation and the widespread adoption of Artificial Intelligence. The primary objective of this paper is to provide insights into the relationship between innovation and employment by proposing a conceptual framework and by discussing the state of the art of the debates and analyses surrounding this topic.
Keywords: O33; 330; Technology; employment; compensation theory; AI; robot